Comprehensive Analysis of Global Industrial Investment Funds: Risk Adjusted Performance Evaluation Based on Statistical Tools 2017-2021 - Diamastuti, Fletcher; Ismail, Tripathi (Journal of Global Economy, Business and Finance, 2024)
This study delves into the intricate landscape of equity mutual funds, employing a comprehensive analysis of top-performing schemes from ten prominent Asset Management Companies (AMCs) over a five-year period (2017-2021). Using a robust methodology that integrates risk and return assessments, the study employs statistical tools such as standard deviation, beta, Sharpe ratio, Treynor ratio, Jensen's alpha, Fama index, and M2 measures to evaluate the risk-adjusted performance of selected funds against the benchmark index Nifty 50. The findings reveal that despite market fluctuations in 2018, certain schemes, notably Axis Blue Chip Fund Direct Plan Growth and UTI Flexi Cap Fund Direct Growth, demonstrated resilience and outperformed the benchmark, offering investors a favourable risk-return profile. The study aids investors in making informed decisions by providing insights into historical performance, emphasizing the importance of thorough research before venturing into equity mutual fund investments.